The creativity of waste management in Payakumbuh City, West Sumatera - Moh. Ilham A. Hamudy; Mujaeni Mujaeni (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Payakumbuh City continues to struggle with its waste management problem despite winning several prestigious Adipura awards. The local government has issued various handling instruments; therefore, it takes practical efforts to deal with it. This study’s objective was to find a solution to the waste problem in Payakumbuh City, West Sumatra. With descriptive methods and qualitative approach, the study found not a few unscrupulous citizens still littering and not complying with the provisions of the disposal time that has been set in Payakumbuh Regional Regulation Number 4 of 2014. Besides including increasing community involvement Payakumbuh City is making several improvements. On the other side, some innovation and creativity were needed to solve the problem. The innovations and creativity were in two aspects: law enforcement and its residents’ involvement, by promoting waste sorting, deployment of biopores, establishing waste banks, plastic waste processing, and composting. The two aspects must be supported by the provision of cross-subsidies for recycled products from the waste banks; facilitation of organic waste management training to the waste bank management community; and the establishment of a regional waste and fertilizer company a synergy between cleanliness, renewable energy, and agriculture.